Pengaruh Intellectualcapital Dan Ukuran Perusahaan Terhadap Nilai Perusahaan Dengan Kinerja Keuangan Sebagai Variabel Intervening - Ratnawati Raflis; Aladin laia (GLOBAL SCIENTS PUBLISHER, 2025)
This study aims to analyze the influence of intellectual capital and company size on firm value, with financial performance as an intervening variable, in the food and staple retail sector listed on the Indonesia Stock Exchange during the 2020–2024 period. The research uses a descriptive quantitative approach with secondary data derived from annual financial reports. The sampling technique applied is the saturated sample method (census), and data analysis is conducted using SPSS version 21. The independent variables in this study are intellectual capital and company size; the dependent variable is firm value; and financial performance serves as the intervening variable. The analytical methods include multiple linear regression, t-test, coefficient of determination (R²), and the Sobel test to evaluate the mediation effect. The findings indicate that both intellectual capital and company size do not significantly affect firm value. Financial performance also shows a weak influence on firm value. However, company size has a significant impact on firm value when mediated by financial performance. These results are expected to contribute to the academic literature and provide practical insights for management and investors in making strategic decisions aimed at enhancing firm value.